In silico Analysis of Transcription Factor Mutants in Saccharomyces cerevisiae - Manoharan, Lokeshwaran (My University, 2011)
Transcriptional regulation of metabolism is considered to be one of the key aspects in controlling the behavior of the cells in response to different environmental conditions. It is important to figure out which transcription factors are involved in regulating the metabolic process in which condition to better understand the relation between regulation and metabolism. This has been addressed through this study in Saccharomyces cerevisiae primarily by computational simulations using regulatory genome-scale model containing regulatory interactions between 961 metabolites [348 genes and 57 transcription factors]. This regulatory model was simulated for gene expression predictions in five different environmental conditions for all available TF mutants and wildtype which accounts for [(57+1)*5] 290 assays/conditions. These gene expression predictions from the regulatory model in those assays are then integrated with the corresponding metabolic model [comprising 798 metabolites, 619 genes] optimizing for maximal growth. While the integration of other conditions were mostly unsuccessful, it was the regulatory predictions from the minimal media condition with galactose as the carbon source which seemed to properly simulate the crab-tree effect in case of the wildtype observed through the flux of ethanol production. It was found that only for the TF-KO mutant ΔMET4 there was a tremendous shift in metabolism from respiration towards fermentation in this particular condition. There were also several inconsistencies with the similar experimental research work achieved through 13C flux analysis of TF mutants in Saccharomyces cerevisiae. It was understood from this study that the regulatory model is highly incomplete. A more complete regulatory model would be absolutely necessary for proper integration of regulatory and metabolic models that can emulate real-time
Keywords: Livsvetenskaper; Industriell bioteknik; Life Science; Industrial Biotechnology